Ecomusicology as a Framework for Decolonizing Music Learning: Insights from Tembang Bocah Banyumasan - Fajry Sub'haan Syah Sinaga; Chamil Arkhasa Nikko Mazlan; Aziz Kurniawan; Hendri Purbo Waseso; Suparjo (Journal of Music Science, Technology, and Industry, 2026)
Purpose: This conceptual study aims to explore ecomusicology as a framework for decolonizing music learning, with Tembang Bocah Banyumasan serving as a case to demonstrate how local musical practices can inform culturally and ecologically grounded pedagogy. Method: The study employs a theoretical-analytical approach, reviewing literature on ecomusicology, decolonial music education, and Indonesian children’s songs, and synthesizing insights from Tembang Bocah to identify links between musical, cultural, and ecological values. Result and Discussion: Analysis shows that integrating Tembang Bocah into music learning promotes multidimensional learning, including musical skill development, local cultural understanding, and ecological awareness. This approach challenges Western-centric pedagogical norms and supports the internalization of moral, social, and environmental values in learners. Implication: The findings suggest that educators can use local songs to preserve cultural heritage, foster ecologically conscious learning, and implement contextually relevant, decolonized music education. This model offers potential adaptation for other local contexts globally.